Effects of the anthropometric and kinematic parameters on 50 m freestyle swimming performances - Hasan Akkus; Metin Ozlu (Türk Spor ve Egzersiz Dergisi)
The aim  of  this  study  was to  determine  the  effects of the anthropometric and  kinematic  parameters on 50 m  freestyle swimming performances in swimmers. The  study  group  of  the  research  consists  of 31  students,  whose  ages  are 23.29 ± 2.65 years,  who  are studying  in School  of  Physical  Education and Sports, Selçuk University, and  who  swim  at  least  for  4  years. In the study, body fat percentage making the various anthropometric measurements on the students, their body fat percentages and body compositions were determined. After 50 m freestyle swimming, the scores of the students were recorded. During these measurements, the students were monitored by means of video camera and their arm cycles were also determined. Stroke rate, tine of 50 m freestyle swimming, and Pearson correlation coefficient of anthropometric variables were calculated. In assessment of the results of   correlation analysis, the range of 0.30-0.70 was defined as middle level relationship and range of 0.70-1.00 as high level relationship. In this study carried out to measure the effect of stroke rates of 50 m freestyle swimmers on performance, a negative middle level relationship was observed between body weight and time of 50 m freestyle swimming. This relationship indicates that when body weight increases, freestyle swimming performance will improve.  In addition, the fact that the swimmers in this study have a endo-meso body type is an important finding pointing out the performance increase.